Drug development of nonalcoholic fatty liver disease: challenges in research, regulatory pathways, and study endpoints. (1st February 2021) - Do, Albert; Ilagan-Ying, Ysabel C.; Mehal, Wajahat Z.; Lim, Joseph K.
ABSTRACT: Introduction: The growing prevalence of nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis (NASH), and its association with obesity as a metabolic disease contributes to harmful outcomes and healthcare resource burden worldwide. For this reason, there is an urgent need to develop new therapies. Identification of treatment targets, research design, endpoints definitions and assessments, and supportive regulatory pathways for drug approval all play prominent roles in shaping efforts in drug discovery, investigation, and approval. Areas covered: In this perspective, the authors enumerate key challenges of NAFLD clinical research and offer a conceptual framework to address these issues which arise during clinical trials. Expert opinion: With the anticipated significant healthcare and costs burden that NAFLD will impose throughout the world, the diagnostics and drug development processes need to be accelerated. Important measures to improve clinical trial research include standardization of case definitions, comprehensive and granular covariate data collection, quality study development incorporating novel trial designs, and quality data reporting. The authors believe that these actions will accelerate understanding, development, and ultimately approval of efficacious treatments.